Operating Conditions Affecting the Behavior of Wheat Straw Pellets During Slow Pyrolysis Process: a Full Insight - Greco, Gianluca; Di Stasi, Christian; González, Belén; Manyà, Joan J. (Jornada de Jóvenes Investigadores del I3A, 2019)
A deep study on the effects of absolute pressure, peak temperature, gas residence time and gas atmosphere on the pyrolysis behaviour of wheat straw pellets in a bench-scale fixed-bed reactor has been carried out.